Erythropoietin attenuates axonal injury after middle cerebral artery occlusion in mice. (3rd June 2017) - Wang, Rongliang; Zhao, Haiping; Li, Jincheng; Duan, Yunxia; Fan, Zhibin; Tao, Zhen; Ju, Fei; Yan, Feng; Luo, Yumin
Abstract: Objective: Erythropoietin (EPO) confers potent neuroprotection against ischemic injury through a variety of mechanisms. However, the protective effect of EPO on axons after cerebral ischemia in adult mice is rarely covered. The purpose of this study was to investigate the potential neuroprotective effects of EPO on axons in mice after cerebral ischemia. Methods: A total of 30 adult male C57 BL/6 mice were treated with EPO (5000 IU/kg) or vehicle after transient middle cerebral artery occlusion (MCAO). The mortality rate of each experimental group was calculated. Neurological function was assessed by Rota-rod test. Frozen sections from each mouse brain at 14 days after reperfusion were used to evaluate the fluorescent intensity of myelin basic protein (MBP) and neurofilament 200 (NF-200). Immunofluorescence staining and Western blotting were used to assess the protein level of β-amyloid precursor protein (β-APP) and glial fibrillary acidic protein (GFAP), a marker of mature astrocytes. The protein levels of the myelin-derived growth inhibitory proteins, neurite growth inhibitor-A (Nogo-A), myelin-associated glycoprotein (MAG) and oligodendrocyte-myelin glycoprotein (OMG) were also examined by Western blot after MCAO. Results: The survival rate of the vehicle group 14 days after cerebral ischemia-reperfusion was 50%, which increased to 80% after EPO treatment at the start of reperfusion. EPO improved neurobehavioral outcomes at days 3 and 7 after MCAO was compared with the vehicle group ( P  < 0.05). Furthermore, EPO ameliorated demyelination, demonstrated by upregulation of the MBP/NF-200 ratio. Meanwhile, increased levels of β-APP, GFAP, Nogo-A, and MAG after MCAO were reduced by EPO treatment ( P  < 0.05). Conclusion: EPO treatment attenuates axonal injury and improves neurological function after cerebral ischemia in adult mice.